In Vivo Role of Neutrophil Extracellular Traps in Antiphospholipid Antibody–Mediated Venous Thrombosis. Issue 3 (27th February 2017) - Meng, He; Yalavarthi, Srilakshmi; Kanthi, Yogendra; Mazza, Levi F.; Elfline, Megan A.; Luke, Catherine E.; Pinsky, David J.; Henke, Peter K.; Knight, Jason S.
Abstract : Objective: Antiphospholipid syndrome (APS) is a leading acquired cause of thrombotic events. Although antiphospholipid antibodies have been shown to promote thrombosis in mice, the role of neutrophils has not been explicitly studied. The aim of this study was to characterize neutrophils in the context of a new model of antiphospholipid antibody–mediated venous thrombosis. Methods: Mice were administered fractions of IgG obtained from patients with APS. At the same time, blood flow through the inferior vena cava was reduced by induction of stenosis. Resulting thrombi were characterized for size and neutrophil content. Circulating factors and the vessel wall were also assessed. Results: As measured by both thrombus weight and thrombosis frequency, mice treated with IgG from patients with APS (APS IgG) demonstrated exaggerated thrombosis as compared with control IgG–treated mice. Thrombi in mice treated with APS IgG were enriched for citrullinated histone H3 (a marker of neutrophil extracellular traps [NETs]). APS IgG–treated mice also demonstrated elevated levels of circulating cell‐free DNA and human IgG bound to the neutrophil surface. In contrast, circulating neutrophil numbers and markers of vessel wall activation were not appreciably different between APS IgG–treated mice and control mice. Treatment with either DNase (which dissolves NETs) or a neutrophil‐depleting antibody reduced thrombosis in APS IgG–treated mice to the level in control mice. Conclusion: These data support a mechanism whereby circulating neutrophils are primed by antiphospholipid antibodies to accelerate thrombosis. This line of investigation suggests new, immunomodulatory approaches for the treatment of APS.